2019
DOI: 10.1242/jcs.221606
|View full text |Cite
|
Sign up to set email alerts
|

The N-cadherin interactome in primary cardiomyocytes as defined using quantitative proximity proteomics

Abstract: The junctional complexes that couple cardiomyocytes must transmit the mechanical forces of contraction while maintaining adhesive homeostasis. The adherens junction (AJ) connects the actomyosin networks of neighboring cardiomyocytes and is required for proper heart function. Yet little is known about the molecular composition of the cardiomyocyte AJ or how it is organized to function under mechanical load. Here, we define the architecture, dynamics and proteome of the cardiomyocyte AJ. Mouse neonatal cardiomyo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 89 publications
3
29
1
Order By: Relevance
“…This study was followed by many others, including an investigation of the Hippo signaling pathway in which phosphorylation-specific interactions could be detected in the absence of sustained signal, revealing a propensity for signal amplification in BioID experiments (19,55). Since its initial development, BioID has been widely used to explore proximal associations in both large and small-scale experimentations in various experimental models (reviewed in (20)) that importantly now include the characterization of the proteome composition and organization of membraneless organelles, including focal adhesions (56) and cell junctions (57)(58)(59)(60), the centrosome (61, 62), P-bodies and stress granules (63), and the generation of a draft proximity map of a human cell (64). As we discuss in the later sections, continued development of this technology has enabled the identification of more active enzymes and permitted the implementation of new assay designs.…”
Section: Downloaded Frommentioning
confidence: 99%
“…This study was followed by many others, including an investigation of the Hippo signaling pathway in which phosphorylation-specific interactions could be detected in the absence of sustained signal, revealing a propensity for signal amplification in BioID experiments (19,55). Since its initial development, BioID has been widely used to explore proximal associations in both large and small-scale experimentations in various experimental models (reviewed in (20)) that importantly now include the characterization of the proteome composition and organization of membraneless organelles, including focal adhesions (56) and cell junctions (57)(58)(59)(60), the centrosome (61, 62), P-bodies and stress granules (63), and the generation of a draft proximity map of a human cell (64). As we discuss in the later sections, continued development of this technology has enabled the identification of more active enzymes and permitted the implementation of new assay designs.…”
Section: Downloaded Frommentioning
confidence: 99%
“…This condition is similar to the one recently reported for two APE1 protein interactors, namely XRCC6 and XRCC5, which have been similarly demonstrated to bind both to RNA/DNA as well as to about 300 proteins 33 . Other examples of proteins having hundreds of interactors (as deduced by a single immunocapture experiment) are already present in the scientific literature [34][35][36][37] . On the other hand, this final list, of direct or indirect APE1-binding partners, contained about 100 proteins whose capability to interact (directly or indirectly) with APE1 was already ascertained by different experimental approaches ( Supplementary Table S3).…”
mentioning
confidence: 98%
“…The Arp2/3-nucleated filaments have been proposed to grow using Ena/Vasodilator-stimulated phosphoprotein(VASP) proteins (Scott et al, 2006;Leerberg et al, 2014) and to then be reconfigured from a branched to a bundled array by an N-WASP-dependent mechanism (Kovacs et al, 2011;Brieher and Yap, 2013). This model is challenged, however, by observations that mature AJs are depleted of Arp2/ 3 (Verma et al, 2004;Hansen et al, 2013) and by proteomics analyses that have failed to identify Arp2/3, neogenin, N-WASP, or a-actinin-4 in association with cadherin tails (Van Itallie et al, 2014;Guo et al, 2014;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There are also uncertainties concerning the configuration and dynamics of F-actin in AJs. Platinum replica electron microscopy (EM) identified a pool of branched F-actin at different types of AJs, including at pAJs, of endothelial cells (Efimova and Svitkina, 2018), while other EM studies have suggested that AJs are directly associated with tensile actin bundles (Yonemura et al, 1995;Buckley et al, 2014;Choi et al, 2016;Li et al, 2019). With respect to dynamics, fluorescence recovery after photobleaching (FRAP) and fluorescence loss after photoactivation (FLAP) experiments with Madin Darby Canine Kidney (MDCK) cells showed that AJ-associated F-actin recovers with a half-life of seconds (Yamada et al, 2005), a rate that corresponds to that of the branched F-actin in lamellipodia (Lai et al, 2008;Fritzsche et al, 2013).…”
Section: Introductionmentioning
confidence: 99%